Research on strata movement control in deep areas of super-thick and weak-cemented overlying strata during local backfill mining—A case study based on Yingpanhao Coal Mine - Leixiang Peng; Guojian Zhang; Huaiwen Wang; Shuo Sun; Yan Zhang; Zhiyong Liu; Zhi-yang Wang (Results in Engineering, 2025)
Deep filling mining is not only affected by the coupling effect of high ground stress and water environment and its own material properties, but also the mining scheme will have different influences on the stress evolution of overlying rocks and surface subsidence. Therefore, this paper studies the secondary compression deformation characteristics of the composite lithology gangue filling body under the coupling effect of high in-situ stress and water environment and establishes a PFC-FLAC coupling model for local filling mining in Yingpanhao Coal Mine to study the influence law of the local filling mining method and the secondary compression deformation of the composite lithology gangue filling body on the control of rock layer movement. Results demonstrate that a stress field of “saddle-stress arch-mushroom arch” is formed in overlying strata when replacing coal resources by the “filling-caving-caving” mining technique. The collaborative effect of fillers and coal pillars is represented as saddle stress, while the collaborative effect of composite carrier and key layers of overlying strata is characterized by mushroom arch stress. They not only weaken the stress concentration on coal pillars, but also decreases risks of geological disasters while controlling surface subsidence effectively. This study also finds that the surface subsidence area expands by 8.7 %∼9.8 % while the secondary compres-sion ratio reaches 7.4∼7.6 %.Therefore, mining technique shall be chosen reasonably during exploitation of coal mines. Weakening secondary compressive deformation of fillers in compound lithologic gangue in advance has high practical values to safe mining of coal resources and environmental protection.